Efektivitas Naskah Dinas Arahan dalam Meningkatkan Kinerja Organisasi: Studi Kasus di Instansi Pemerintahan - A, Ariana; Hasibuan, Nurul Atika; Manik, Khalid Samahangga; Chaidir, Muhammad; Darmansah, Tengku (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study examines the effectiveness of directive official memos in enhancing organizational performance within government institutions. Structured administrative communication plays a vital role in ensuring seamless coordination, improving task clarity for employees, and optimizing responsiveness to policy shifts. Using a qualitative approach with thematic analysis, this study explores strategic communication patterns within official documents and regulatory frameworks to identify mechanisms that contribute to bureaucratic efficiency and organizational stability. The findings indicate that institutions implementing directive official memos systematically experience improved productivity and work effectiveness. Clear guidance enables employees to comprehend instructions more accurately, fostering adaptive organizational responses to change. Additionally, maintaining a consistent administrative communication standard strengthens work structure, facilitates optimal policy implementation, and ensures that government institutions operate efficiently while aligning with institutional objectives.